THE ROLE OF BACTERIAL TRANSLOCATION AND MICROBIOTA IN INTESTINAL BLOCKAGE: AN EXPERIMENTAL STUDY. - Ranjan, Jitendra Kumar; Kar, Pritam (Student's Journal of Health Research Africa, 2024)
Background: The objective of this study is to investigate bacterial typing (BT) in the context of infectious diseases (I.O.), including the identification of pathogens, their transmission routes, and common characteristics. Methods: The study included 90 albino male rats in three groups: control (GI), simple ileal blockage (GII), and strangulated (GIII). Various surgical procedures were conducted under intramuscular ketamine anesthesia. Biochemical analysis measured CRP, IL-10, and oxidant and antioxidant activities. Histopathology assessed mucosal injury and inflammatory cell infiltration. Bacteriological examination identified bacterial species and CFU by cultivating tissue and blood samples. Observation: Strangulated intestinal obstruction increased bacterial proliferation, oxidative stress indicators, and IL-10 response, according to the study. The mean CFU/g of luminal bacteria count was 8.8 × 108 in GI, 5.6 × 1010 in GII, and 1.4 × 1012 in GIII. Mean MDA levels were 5.5 ± 0.5 in GI, 12.0 ± 1.9 in GII, and 21.9 ± 1.0 in GIII. The mean GPx levels were 125 ± 30 in GI, 165 ± 40 in GII, and 150 ± 35 in GIII. The mean IL-10 levels were 50 ± 15 in GI, 36 ± 12 in GII, and 9 ± 3 in GIII. Bacterial translocation was polymicrobial, with 49% in GII and 60% in GIII. Most enteric bacteria were E. coli, 42.2% in GII and 45.5% in GIII. Conclusion: Intestinal obstruction causes bidirectional bacterial translocation through a systemic portal, with a three-hit model primarily responsible for the ensuing inflammatory response. A non-selective marker of possible I.O. cases is the C-reactive protein. The C-reactive protein serves as an indicator of both Impaired blood flow to the tissues and the level of BT. Recommendations: Further studies should focus on developing more specific markers for early diagnosis of intestinal obstruction subtypes and exploring potential therapeutic interventions to manage bacterial translocation effectively